A genome wide survey supports the involvement of large copy number variants in schizophrenia with and without intellectual disability. Issue 8 (25th September 2013) - Derks, Eske M.; Ayub, Muhammad; Chambert, Kimberly; Del Favero, Jurgen; Johnstone, Mandy; MacGregor, Stuart; Maclean, Alan; McKechanie, Andrew G.; McRae, Allan F.; Moran, Jennifer L.; Pickard, Benjamin S.; Purcell, Shaun; et al.
Abstract Background Copy number variants (CNVs) have been shown to play a role in schizophrenia and intellectual disability. Methods We compared the CNV burden in 66 patients with intellectual disability and no symptoms of psychosis (ID‐only) with the burden in 64 patients with intellectual disability and schizophrenia (ID + SCZ). Samples were genotyped on three plates by the Broad Institute using the Affymetrix 6.0 array. Results For CNVs larger than 100 kb, there was no difference in the CNV burden of ID‐only and ID + SCZ. In contrast, the number of duplications larger than 1 Mb was increased in ID + SCZ compared to ID‐only. We detected seven large duplications and two large deletions at chromosome 15q11.2 (18.5–20.1 Mb) which were all present in patients with ID + SCZ. The involvement of this region in schizophrenia was confirmed in Scottish samples from the ISC study (N = 2, 114; 1, 130 cases and 984 controls). Finally, one of the patients with schizophrenia and low IQ carrying a duplication at 15q11.2, is a member of a previously described pedigree with multiple cases of mild intellectual disability, schizophrenia, hearing impairment, retinitis pigmentosa and cataracts. DNA samples were available for 11 members of this family and the duplication was present in all 10 affected individuals and was absent in an unaffected individual. Conclusions Duplications at 15q11.2 (18.5–20.1 Mb) are highly prevalent in a severe group of patients characterized by intellectual disability and comorbid schizophrenia. It is also associated with a phenotype that includes schizophrenia, low IQ, hearing and visual impairments resembling the spectrum of symptoms described in "ciliopathies." © 2013 Wiley Periodicals, Inc.